Relasi Kepemimpinan dan Kultur Sekolah - Rohmat Rohmat (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
Abstract: The dynamics of scholl has very strong links with leadership. The dominant factor to form a school character and has a competitive advantage in the academic field id dependent on the ability of the proncipal increating a school culture. Establishment of schoool culture begins from building mindset of all school personnel to make changes. This have initiated by school's principal through ongoing innovation. Establishment of an effective school culture requires a long duration efforts and carried simultaneously on all aspects of the schools and the main factor is the headmaster. Finally, the leadership has a very strong relationship in a set up a school culture. Without leadership development, meaningful academic change will not hapen and school become just a passive static routine. Keywords: School Culture, Leadership.